Answer:
We conclude that both the points (0, -27) and (-9, 0) are on the line as both the points satisfy the equation.
Explanation:
Given the equation
3y - 9x = -81
substituting the point (0, -27) in the equation
3y - 9x = -81
3(-27) - 9(0) = -81
-81 - 0 = -81
-81 = -81
L.H.S = R.H.S
so, the point satisfies the equation.
Thus, the point (0, -27) is on the line
now substituting the point (-9, 0) in the equation
3y - 9x = -81
3(0) - 9(-9) = -81
0 - 81 = -81
-81 = -81
L.H.S = R.H.S
so, the point satisfies the equation.
Thus, the point (-9, 0) is on the line
Therefore, we conclude that both the points (0, -27) and (-9, 0) are on the line as both the points satisfy the equation.